Effect of Graded Levels of Baobab (Adansonia digitata) Seed Meal on the Growth Performance and Production Economic Analysis of Broiler Chickens - Bale , Jerry Sarven; Mancha, Yusuf Pam; Sanusi, Mohammed; Doma, Umar Dass (International Journal of Poultry Science, 2013)
A feeding trial was conducted to determine the effect of graded levels of baobab seed meal on growth performance and cost benefit in broiler chicken production. A total of two hundred one-week old broiler chicks of the Anak breed were randomly distributed to five dietary treatments and replicated four times with 10 birds each for a period of 8 weeks. Baobab seed meal was included in the broiler chicken diets at 0, 10, 20, 30 and 40% levels designated as diets 1, 2, 3, 4 and 5, respectively for both the starter and finisher phases. At the starter phase, feed intake (65.18-71.73 g), daily weight gain (30.36-36.16 g) and feed conversion ratio (1.96-2.39) were not significantly (p>0.05) affected by the dietary treatments. However, at finisher phase, the daily feed intake (133.40-148.40 g) and weight gain (37.23-55.00 g) were significantly affected at (p